2019
DOI: 10.1002/pbc.27886
|View full text |Cite
|
Sign up to set email alerts
|

Emicizumab prophylaxis among infants and toddlers with severe hemophilia A and inhibitors—a single‐center cohort

Abstract: Background: Emicizumab is a bispecific antibody that bridges factor IXa and factor X to restore hemostasis in patients with hemophilia A (HA). Its efficacy and safety have been proven in multicenter trials. However, real world data regarding its use in very young children are currently lacking. Ancillary test results for monitoring emicizumab's hemostatic effect and their clinical correlations are scarce. Methods:Children with HA and inhibitors treated by emicizumab were prospectively followed at our center. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
127
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(137 citation statements)
references
References 27 publications
6
127
1
Order By: Relevance
“…In the last several years, novel therapeutics have been evaluated in clinical trials, among which the bispecific monoclonal antibody, emicizumab, has been licensed for the prevention of bleeding in children and adults with haemophilia with and without inhibitors. Recent studies indicate emicizumab is safe and effective for prophylaxis in infants with haemophilia A 15,16 and in immune tolerance induction (ITI) in inhibitor patients, 16,17 and, while costly, is cost-effective in those with inhibitors. 13,14 Whether bleed frequency and bleed severity, long-term joint health and quality of life are comparable to that achieved with factor VIII, therefore, remains unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the last several years, novel therapeutics have been evaluated in clinical trials, among which the bispecific monoclonal antibody, emicizumab, has been licensed for the prevention of bleeding in children and adults with haemophilia with and without inhibitors. Recent studies indicate emicizumab is safe and effective for prophylaxis in infants with haemophilia A 15,16 and in immune tolerance induction (ITI) in inhibitor patients, 16,17 and, while costly, is cost-effective in those with inhibitors. 13,14 Whether bleed frequency and bleed severity, long-term joint health and quality of life are comparable to that achieved with factor VIII, therefore, remains unknown.…”
mentioning
confidence: 99%
“…13,14 Whether bleed frequency and bleed severity, long-term joint health and quality of life are comparable to that achieved with factor VIII, therefore, remains unknown. Recent studies indicate emicizumab is safe and effective for prophylaxis in infants with haemophilia A 15,16 and in immune tolerance induction (ITI) in inhibitor patients, 16,17 and, while costly, is cost-effective in those with inhibitors. 18 Yet, there is limited experience with emicizumab in breakthrough bleeding rates and surgical hemostasis in those with and without inhibitors.…”
mentioning
confidence: 99%
“…In both case series, no spontaneous bleeds were reported for up to 52 weeks after initiation of QW emicizumab prophylaxis in a total of 15 male HA children with high-titer FVIII-inhibitors. 37,38 In the phase 3 HAVEN 2 trial, enrolling 88 HA children (2-12 years of age) with high-titer FVIII-inhibitors, 68 patients received the QW dosing regimen for a median efficacy period of 57.6 weeks (range 17.9-92.6). Among them, 94.7% had zero treated bleeds, and 72.3% experienced zero bleeds, whether they were treated or not.…”
Section: Efficacy Of Emicizumab In Children With Severe Hemophilia a mentioning
confidence: 99%
“…Most treated bleeds observed in these studies were traumatic bleeds, with half of them being joint bleeds, which resolved after few injections of BPA. 32,37,38 When comparing to other dosing regimens used in the HAVEN 2 study, we can notice that the Q4W dosing regimen performed less well than both QW and Q2W dosing regimens in terms of pharmacokinetic profile, which resulted in lower efficacy over bleeding prevention (Table 1; Figure 1). 32 Interestingly, studies revealed that emicizumab prophylaxis considerably reduced target joints.…”
Section: Efficacy Of Emicizumab In Children With Severe Hemophilia a mentioning
confidence: 99%
See 1 more Smart Citation